Surface Inorganic Iodine Speciation in the Indian and Southern Oceans From 12°N to 70°S - Chance, Rosie; Tinel, Liselotte; Sarkar, Amit; Sinha, Alok K.; Mahajan, Anoop S.; Chacko, Racheal; Sabu, P.; Roy, Rajdeep; Jickells, Tim D.; Stevens, David P.; Wadley, Martin; Carpenter, Lucy J. (Frontiers in Marine Science, 2020)
Marine iodine speciation has emerged as a potential tracer of primary productivity, sedimentary inputs, and ocean oxygenation. The reaction of iodide with ozone at the sea surface has also been identified as the largest deposition sink for tropospheric ozone and the dominant source of iodine to the atmosphere. Accurate incorporation of these processes into atmospheric models requires improved understanding of iodide concentrations at the air-sea interface. Observations of sea surface iodide are relatively sparse and are particularly lacking in the Indian Ocean basin. Here we examine 127 new sea surface (10 m depth) iodide and iodate observations made during three cruises in the Indian Ocean and the Indian sector of the Southern Ocean. The observations span latitudes from ~12oN to ~70oS, and include three distinct hydrographic regimes: the South Indian subtropical gyre, the Southern Ocean and the northern Indian Ocean including the southern Bay of Bengal. Concentrations and spatial distribution of sea surface iodide follow the same general trends as in other ocean basins, with iodide concentrations tending to decrease with increasing latitude (and decreasing sea surface temperature). However, the gradient of this relationship was steeper in subtropical waters of the Indian Ocean than in the Atlantic or Pacific, suggesting that it might not be accurately represented by widely used parameterisations based on sea surface temperature. This difference in gradients between basins may arise from differences in phytoplankton community composition and/or iodide production rates. Iodide concentrations in the tropical northern Indian Ocean were higher and more variable than elsewhere. Two extremely high iodide concentrations (1241 and 949 nM) were encountered in the Bay of Bengal and are thought to be associated with sedimentary inputs under low oxygen conditions. Excluding these outliers, sea surface iodide concentrations ranged from 20 to 250 nM, with a median of 61 nM. Controls on sea surface iodide concentrations in the Indian Ocean were investigated using a state-of-the-art iodine cycling model. Multiple interacting factors were found to drive the iodide distribution. Dilution via vertical mixing and mixed layer depth shoaling are key controls, and both also modulate the impact of biogeochemical iodide formation and loss processes.